Studies on the fusability of coal ash. - Herrera, D.L. Pugal
A study, which aims to develop a technology for the preparation of a high quality adsorbent for SOx using coal ash to control air pollution caused by coal-fired thermal power plants in the Philippines, is currently being jointly undertaken by ITDI and HNIRI. During its first year of implementation, the physical, chemical and thermal characteristics of Philippine and Japanese coal ash samples were determined. Results show that Philippine coal as samples are of the silicoaluminuous type while that of the Japanese coal samples are of the aluminosiliceous type. Three (3) common major elements, namely, quartz, mullite and hematite are found in all coal ash samples. A correlation between the melting point and chemical composition of the coal ash samples shows that the coal ash samples having a low acid base index resulted in high melting points.